Wolf bells : a novel - Zumas, Leni, 1972- (Algonquin Books of Chapel Hill, 2025)
On a bluff above a river rises The House, where elderly and disabled residents live alongside young people who help out in exchange for free rent. The community is led by a former punk singer who never wanted to be responsible for anyone yet now finds herself the caretaker of this precarious collection of lives. It's not a family, exactly, but it's got the complicated, sometimes painful, sometimes hilarious, dynamics of kinship. When two kids--Nola and her little cousin James--show up on The House's back porch in need of refuge, the whole experiment is thrown into question. All are welcome here, or that was the idea. But the authorities are looking for these children,and The House's finances are teetering on the edge.